Hidden behavioural characteristics of financial awareness among the Hungarian population - Csiszárik-Kocsir, Ágnes; Varga, János; Bagó, Péter (Vezetéstudomány / Budapest Management Review, 2024)
The pandemic has significantly rewritten the lives of all economic actors. similar phenomenon occurred in the past, when the economic crisis of 2008 compelled a fundamental shift in the trajectory of the life. The sudden closures required new life organisation choices, which called for different competences and skills. The loss of jobs was a prominent feature of both events, resulting in challenges for families. The importance of savings was highlighted, and individuals were compelled to make responsible choices about consumption and become more conscious in many respects. All these challenges have once again highlighted the importance of financial literacy and financial awareness. This study investigates the perceived significance of financial knowledge and understanding, as well as the perception of certain dimensions of it, along the subjectively perceived characteristics of thrift and prudence, and how these factors interact with each other among Hungarian survey respondents.